THU0228 Tofacitinib, an Oral Janus Kinase Inhibitor: Post-HOC Analyses of Efficacy and Safety of Monotherapy Versus Combination Therapy in a Phase 3 Rheumatoid Arthritis Population. (23rd January 2014) - Keystone, E.; Fleischmann, R.; van Vollenhoven, R.; Kremer, J.; Gruben, D.; Bradley, J.; Riese, R.; Mebus, C.; Wallenstein, G.; Zwillich, S. H.; Benda, B.; Krishnaswami, S.
Abstract : Background: Tofacitinib is a novel oral Janus kinase (JAK) inhibitor for the treatment of rheumatoid arthritis (RA). Phase (P) 2 and 3 studies demonstrated tofacitinib is effective and has a manageable safety profile as both monotherapy and in combination with nonbiologic disease-modifying antirheumatic drugs (DMARDs). Objectives: To assess whether there are relative differences in efficacy or safety between mono- and combination therapy in RA patients (pts) with an inadequate response (IR) to DMARDs. Methods: Pooled tofacitinib data from three combination therapy P3 studies (≈2100 pts) (ORAL Sync, Standard and Scan) were compared to one monotherapy P3 study (≈600 pts) (ORAL Solo), all DMARD IR pts. The proportion of pts achieving ACR20, 50 and 70, DAS28-4(ESR) (DAS)-defined remission and low disease activity (LDA) (DAS <2.6 and ≤3.2, respectively), and HAQ-DI improvement ≥0.22 were assessed at Month 3. Month 0–3 incidence of adverse events (AEs), discontinuation (d/c) due to AEs, and serious AEs (SAEs) were compared (true placebo [PBO] only to Month 3). Data were analysed by a meta-analytic (MA) approach using log odds ratio (LOR) as the outcome measure. For each study, the LORs and corresponding sampling variances were calculated for tofacitinib 5 mg twice daily (BID) vs PBO and tofacitinib 10 mg BID vs PBO. The MA model included effects of background (monotherapy vs combination) and dose (5 mg BID vs 10 mg BID), and employed inverse variance weighting and restricted maximum-likelihood estimation. The model estimated difference in LOR between mono- and combination therapy was exponentiated and expressed as odds ratios (ORs) with 95% confidence intervals (CIs). Results: Demographic and baseline (BL) disease characteristics of pts across the four studies were generally similar, except geographic region of enrolment; the highest level of mean BL values of joint counts, CRP, HAQ and DAS were seen in the monotherapy study (DAS 6.69 vs 6.29-6.46 with monotherapy vs combination therapy, respectively). In the efficacy and safety analyses (Figure), point estimates for the ORs ranged from 1.0–1.3 for rates of ACR20/50/70, LDA, HAQ and AEs, 1.9 for DAS-defined remission and 0.5 for d/c due to AEs and SAEs. Across all endpoints, the CIs included 1, indicating similar response and risk rates for tofacitinib mono- and combination therapy. Image/graph: Conclusions: In this meta-analysis, no statistically significant differences in efficacy or safety endpoints were observed with tofacitinib administered as monotherapy or in combination with DMARDs in DMARD IR pts. A randomised clinical trial directly comparing mono- and combination therapy is warranted to confirm these results. Disclosure of Interest: E. Keystone: None Declared, R. Fleischmann: None Declared, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB, Consultant for: AbbVie, BMS, GSK, MSD, Pfizer, Roche, UCB, J. Kremer: None Declared, D. Gruben Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bradley Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., R. Riese Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., C. Mebus Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., G. Wallenstein Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Zwillich Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., B. Benda Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., S. Krishnaswami: None Declared